Rank conditions for finite group actions on 4-manifolds. (18th April 2022) - Hambleton, Ian; Pamuk, Semra
Abstract: Let M be a closed, connected, orientable topological $4$ -manifold, and G be a finite group acting topologically and locally linearly on M . In this paper, we investigate the spectral sequence for the Borel cohomology $H^*_G(M)$ and establish new bounds on the rank of G for homologically trivial actions with discrete singular set.